Machine Learning and Big Data Analytics in Smart Cities and Healthcare: Applications, Challenges, and Future Directions - Pasupuleti, Vikram; Thuraka, Bharadwaj; Kodete, Chandra Shikhi (2024 International Conference on Computer and Applications (ICCA), 2024)
Machine learning (ML) and big data analytics are playing a pivotal role in transforming both smart cities and healthcare systems by enhancing decision-making, resource optimization, and predictive modeling. In smart cities, these technologies are applied in areas like traffic management, energy optimization, and public safety. In healthcare, ML contributes to predictive diagnostics, personalized medicine, and remote patient monitoring. Despite their potential, these domains face significant challenges, including data privacy concerns, scalability issues, and the interpretability of complex ML models. This paper provides a comprehensive review of the current applications of ML and big data in smart cities and healthcare, identifying shared challenges and exploring the future impact of emerging technologies such as IoT, 5G, and federated learning. Through case studies and analysis, we highlight the key opportunities for interdisciplinary collaboration and discuss how these technologies are shaping the future of urban management and personalized healthcare delivery.